The Influence of Factor Disclosure Environmental, Social and Governance Effects on Corporate Values in Manufacturing Companies in the Automotive Sector Registered in Indonesian:System Literature Review - Reza Utama, Putri; Sintia Putri (Journal of Creative Student Research, 2026)
This study aims to examine the influence of Environmental, Social, and Governance (ESG) disclosure on firm value in listed automotive manufacturing companies in Indonesia using a Systematic Literature Review (SLR) approach. The SLR approach is used to collect, assess, and integrate findings from relevant previous studies, both from national and international journals. The analysis results indicate that environmental disclosure contributes to improving corporate image and investor confidence through the implementation of sustainability practices. Social aspects play a role in strengthening relationships with stakeholders and supporting the sustainability of company operations. On the other hand, effective corporate governance has been shown to reduce agency risk and increase transparency, thus positively impacting firm value. However, several studies show inconsistent findings, influenced by the level of ESG disclosure and the characteristics of each company. In general, this study concludes that the implementation and continuous disclosure of ESG can be a relevant strategy in increasing firm value in the Indonesian automotive sector.